Time in Therapeutic Range of Unfractionated Heparin-Based Therapy in Critically Ill Patients with COVID-19 Pneumonia - Romanová, Tereza; Burša, Filip; Sklienka, Peter; Sagan, Jiří; Vaňková, Michelle; Buršík, Denis; Bílená, Markéta; Pulcer, Martin; Burda, Michal; Máca, Jan (Therapeutics and clinical risk management, 2024)
PURPOSE: Anticoagulation therapy aims to improve the outcome of critically ill patients with severe COVID-19-associated pneumonia. Activated partial thromboplastin time (aPTT) is commonly used to maintain the target therapeutic range of continuous infusion of unfractionated heparin (UFH). The UFH infusion efficacy can be evaluated by determining the time in therapeutic range (TTR) using a modified Rosendaal method. The present study's primary aim was to evaluate TTR based on the aPTT in critically ill patients with severe forms of COVID-19 pneumonia and its influence on survival. The secondary aim was to evaluate the time spent above (TATR) and below the therapeutic range (TBTR). PATIENTS AND METHODS: We performed a retrospective analysis of critically ill patients with COVID-19-associated pneumonia. All patients received a continuous infusion of UFH from the 2nd to 8th day since admission to the ICU. TTR, TATR, and TBTR were calculated using the modified Rosendaal method, and survival days were analyzed by regression (censored after 60 days). RESULTS: Of 103 patients, the median TTR was 49% (IQR 38-63%), TATR 11% (IQR 5-20%), and TBTR 33% (IQR 22-51%). The regression analysis indicated a positive impact of higher TTR and TATR on the number of survival days [β=0.598 (p=0.0367) and β=1.032 (p=0.0208), respectively] and a negative impact of higher TBTR [β=-0.681 (p=0.0033)] on the number of survival days. CONCLUSION: Higher TTR and TATR were associated with better survival of critically ill patients with a severe course of COVID-19-associated pneumonia. Higher TBTR was associated with worse survival in these patients.
Keywords: critical care; COVID-19; pneumonia; unfractionated heparin